2001
DOI: 10.1038/sj.onc.1204867
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C inhibits singlet oxygen-induced apoptosis by decreasing caspase-8 activation

Abstract: Although activation of protein kinase C (PKC) inhibits apoptosis induced by a variety of stimuli including singlet oxygen, the step at which PKC activation interferes with apoptotic signaling is not well de®ned. We have shown previously that caspase-8 and p38 mediate singlet oxygen-induced apoptosis in HL-60 cells. In this study, we investigated the in¯uence of PKC on regulation of the caspase and p38 pathways initiated by singlet oxygen. Singlet oxygen induced Fas clustering and subsequent recruitment of FADD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 82 publications
5
39
0
Order By: Relevance
“…We found that this remaining ASP-induced insulin secretion was inhibited by GF109203, which is an inhibitor of classical PKC subtypes. 27 PKC is involved in insulin secretion by first being activated by glucose through diacylglycerol formed after phosphoinositide hydrolysis instituted by phospholipase C, and then translocated to the cell membrane and activating the exocytosis of insulin. 26 The results thus suggest that ASP stimulates insulin secretion by augmenting the action of glucose to open Ca 2+ and to activate PKC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that this remaining ASP-induced insulin secretion was inhibited by GF109203, which is an inhibitor of classical PKC subtypes. 27 PKC is involved in insulin secretion by first being activated by glucose through diacylglycerol formed after phosphoinositide hydrolysis instituted by phospholipase C, and then translocated to the cell membrane and activating the exocytosis of insulin. 26 The results thus suggest that ASP stimulates insulin secretion by augmenting the action of glucose to open Ca 2+ and to activate PKC.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of protein kinase C (PKC) is known to contribute to glucose-stimulated insulin secretion. 25,26 We found that bisindolylmaleimide (GF109203; 2 mmol/l), which inhibits PKC, 27 inhibited ASP-induced insulin secretion by approximately 30%. Thus, whereas ASP in the absence of GF109203 augmented glucose-stimulated insulin secretion by 7.570.9 nmol/l, the inhibitor reduced the effect of ASP to 4.870.5 nmol/l (Po0.001).…”
Section: Statistics and Calculationsmentioning
confidence: 96%
“…Nevertheless, caspase 8 does not appear to be present in established focal adhesions, nor does caspase 8 activation occur during integrin ligation events during cell spreading. However, caspase 8 is not always activated by DR ligation and membrane recruitmentin fact, the activation of signaling molecules such as Akt (Abreu et al, 2001;Li et al, 2002;Thakkar et al, 2001) or PKC (Gomez-Angelats and Cidlowski, 2001;Miranti et al, 1999;Zhuang et al, 2001;Meng et al, 2002) suppresses activation of caspase 8 and may be involved in DR-mediated signaling to the NFκB, JNK or ERK1/2 pathways (Fig. 4).…”
Section: Do Integrins Communicate With the Ded?mentioning
confidence: 99%
“…Several groups have shown an increasing interest in this field, and many different proteins and protein cascades have been investigated. The PDT-induced mitochondrial release of cytochrome C (Vantieghem et al 1998, Kim et al 1999, Reiners, Jr. et al 2002, caspases (Granville et al 1998, Zhuang et al 2001 and (Bonni et al 1999, Chang & Karin 2001, Hazzalin & Mahadevan 2002.…”
Section: The Impact Of Mapk Signallingmentioning
confidence: 99%